The Impact of Drought Stress on The Growth of Water Spinach (Ipomea Reptans Poir) - Asadudin, David; Lulu Anbiya; Metari Arsitalia; Mahfut (UNIVERSITAS PGRI MADIUN, 2024)
Water spinach (Ipomoea reptans Poir) is a commonly cultivated vegetable in tropical regions like Indonesia. Water spinach faces challenges related to water availability, which can impact various cellular, biochemical, and physiological aspects. Drought can lead to reduced vegetative growth, and a lack of water can inhibit overall plant growth. Therefore, understanding the growth response of water spinach to water stress is crucial for achieving optimal results. This study used a Completely Randomized Design (CRD) with water concentration as the treatment. Water spinach seeds were selected before being sown and transferred to polybags. Irrigation was conducted with five levels of concentration: 100% (300 ml of water), 75% (225 ml of water), 50% (150 ml of water), 25% (75 ml of water), and 0% (0 ml of water). Observations were made at 14 days old with agronomic and anatomical parameters, and the data were analyzed using MANOVA followed by a Tukey post-hoc test at a 5% significance level with SPSS. The results showed that irrigation with 300 ml and 225 ml of water produced the highest number of stomata and the longest stomata size. For stomatal width, treatments of 300 ml, 225 ml, and 75 ml resulted in wider stomata. Meanwhile, for stomatal area, the 225 ml treatment showed the largest stomatal size. However, no significant differences were observed in plant height and leaf number among the treatments. Drought stress affects photosynthesis and plant growth, with increasingly severe impacts as drought intensity rises. Drought results in reduced stomatal number, smaller stomatal size, and inhibited plant growth.